Utilizing Binary Logistic Regression Models for Predicting the Risk Factors of Heart Disease - Kasem Farag; Eman Shuaeib; Husam Aqel; Marfoua Ali (AlQalam Journal of Medical and Applied Sciences, 2025)
With rising yearly death rates, cardiovascular disease (CVD) continues to be a major global health concern. Effective prevention and management of risk factors depend on an understanding of how they interact. Predicting the primary causes of heart disorders, examining the impact of each of these elements, and organizing them according to model choice and classification capabilities were the objectives of this work. To forecast the probability of CVD, a logistic regression model was created. The parameters impacting infection risk were characterized using descriptive analysis. Data were collected from 82 patients at Benghazi Cardiac Centre, comprising 41 infected patients and 41 control subjects selected using the Stephan Thompson Equation. Binary logistic regression analysis, conducted using SPSS 23, identified four significant predictors of cardiac infection: diabetes, BMI, cholesterol level, and blood pressure. The model demonstrated an 89% accuracy in classifying patients. Further research is recommended to investigate the impact of additional factors on cardiac infection risk in this population. مع ارتفاع معدلات الوفيات السنوية، لا تزال أمراض القلب والأوعية الدموية تشكل مصدر قلق صحي عالمي رئيسي. وتعتمد الوقاية الفعالة وإدارة عوامل الخطر على فهم كيفية تفاعلها. وكان التنبؤ بالأسباب الرئيسية لاضطرابات القلب، وفحص تأثير كل من هذه العناصر، وتنظيمها وفقًا لاختيار النموذج وقدرات التصنيف، من أهداف هذا العمل. وللتنبؤ باحتمالية الإصابة بأمراض القلب والأوعية الدموية، تم إنشاء نموذج الانحدار اللوجستي. وتم وصف المعلمات التي تؤثر على خطر الإصابة بالعدوى باستخدام التحليل الوصفي. وتم جمع البيانات من 82 مريضًا في مركز بنغازي للقلب، بما في ذلك 41 مريضًا مصابًا و41 شخصًا من المجموعة الضابطة تم اختيارهم باستخدام معادلة ستيفان طومسون. وقد حدد تحليل الانحدار اللوجستي الثنائي، الذي أجري باستخدام برنامج SPSS 23، أربعة عوامل تنبؤ مهمة للإصابة بالعدوى القلبية: مرض السكري، ومؤشر كتلة الجسم، ومستوى الكوليسترول، وضغط الدم. وأظهر النموذج دقة بنسبة 89٪ في تصنيف المرضى. ويوصى بإجراء المزيد من البحوث للتحقيق في تأثير العوامل الإضافية على خطر الإصابة بالأمراض القلبية